Comparative effect of arginine and/or tryptophan in ovo feeding on hatchability percentage, growth performance and economic importance of commercial broiler - NAYAK, NIBEDITA; RAJINI, R ASHA; EZHILVALAVAN, S; SAHU, AMIYA RANJAN; KIRUBAHARAN, J JOHN (The Indian Journal of Animal Sciences, 2017)
In ovo feeding is the administration of exogenous nutrients into the amnion of the late-term avian embryo so that the avian embryo orally consumes the amniotic fluid (primarily water and albumen protein) prior to pipping the air cell. So the study was carried out to find out the effect of in ovo nutrition on post-hatch performances in broilers. Total 700 fertile eggs of Cobb 400 with uniform egg weight were divided into 5 groups: non-injected control, injected control (0.5 ml of 0.9% normal saline), arginine (0.5 ml of 0.5% arginine), tryptophan (0.5 ml of 0.5% tryptophan) and combination (0.25 ml of 0.5% each of arginine and tryptophan); and injected on 18 d of incubation into amnion. On the 21d, 108 chicks were randomly selected from each treatment in total accounting 540 chicks. The hatchability and hatch weight were studied where arginine had shown a highly significant improved hatch weight and placement weight. There was no significant difference in feed efficiency, but cumulative feed intake was higher in tryptophan and combination groups. Body weight and body weight gain had also resulted significantly in arginine fed in ovo groups up to 21d of age. The broiler farm economy index (BFEI) and broiler feed price ratio (BFPR) were best in tryptophan and arginine in ovo fed groups, respectively.